Peranan Kelompok Tani dalam Peningkatan Status Sosial Petani Padi Sawah di Desa Meraka Kecamatan Lambuya Kabupaten Konawe - Salam, Idrus; Salahuddin, Salahuddin; Saputra, Ikra (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2017)
This study was aimed to investigate (1) the role of group of farmers on improving the social status of rice field farmers (2) how was the social status of rice field farmers at Meraka village (3) the association among the role of group of farmers towards the improvement of social status of rice field farmers at Meraka village, Lambuya, Konawe district. The population was 30 farmers who lived at Meraka village as the sample of this research.The instrument of the study was Sperman rank analysis. The variables observed on this study were the group or farmers and the social status of rice field farmers. The result of this study shows that (1) the utilization of grouping farmers has a positive role on the improvement of social status of rice field farmers (2) the social status of rice field farmers in Meraka village existed on the medium category (3) the role of group of farmers has a significant relationship with the improvement of the social status of rice field farmers in Meraka village, Lambuya, Konawe district.